Moving mountains - when rocks and fluids interact - Engvik, Ane K.; Elvevold, Synnøve; Myhre, Per Inge; Sunde, Øyvind; Austrheim, Håkon (Fram forum, 2021)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

The glacial geomorphology of western Dronning Maud Land, Antarctica - Newall, Jennifer C H; Dymova, Taisiya; Serra, Elena; Blomdin, Robin; Fredin, Hans Ola; Glasser, Neil F; Suganuma, Yusuke; Harbor, Jonathan M; Stroeven, Arjen P (Journal of Maps, 2020)
Reconstructing the response of present-day ice sheets to past global climate change is important for constraining and refining the numerical models which forecast future contributions of these ice sheets to sea-level change. Mapping landforms is an essential step in reconstructing glacial histories. Here we present a new map of glacial landforms and deposits on nunataks in western Dronning Maud Land, Antarctica. Nunataks are mountains or ridges that currently protrude through the ice sheet and may provide evidence that they have been wholly or partly covered by ice, thus indicating a formerly more extensive (thicker) ice sheet. The map was produced through a combination of mapping from Worldview satellite imagery and ground validation. The sub-metre spatial resolution of the satellite imagery enabled mapping with unprecedented detail. Ten landform categories have been mapped, and the landform distributions provide evidence constraining spatial patterns of a previously thicker ice sheet.
Publisher: Taylor & Francis
Keywords: Dronning Maud Land; geomorfologi; innlandsis; klimaendringer; nunataker; paleoglasiologi

Geological mapping of Norway's least explored mountains - Elvevold, Synnøve; Myhre, Per Inge; Engvik, Ane K; Jacobs, Joachim (Fram forum, 2019)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging; nunataker

Vannet som forandret fjellene - Engvik, Ane K (Bergtatt - Ane K. Engviks blogg, 2019)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

The influence of Nunataks on atmospheric boundary layer convection during summer in Dronning Maud Land, Antarctica - Stenmark, Aurora; Hole, Lars Robert; Voss, Paul; Reuder, Joachim; Jonassen, Marius O (Journal of Geophysical Research: Atmospheres, 2014)
The effects of nunataks on temperature profiles and wind patterns are studied using simulations from the Weather Research and Forecasting model. Simulations are compared to hourly observations from an automatic weather station located at the Troll Research Station in Dronning Maud Land. Areas of bare ground have been implemented in the model, and the simulations correspond well with meteorological measurements acquired during the 4 day simulation period. The nunataks are radiatively heated during daytime, and free convection occurs in the overlying atmospheric boundary layer. The inflow below the updraft forces strong horizontal convergence at the surface, whereas weaker divergence appears aloft. In a control run with a completely ice-covered surface, the convection is absent. In situ observations carried out by a remotely controlled balloon and a small model airplane compare well with model temperature profiles, but these are only available over the ice field upwind to the nunatak.
Keywords: Dronning Maud Land; atmosfæren; geofysikk; meteorologi; nunataker; observasjoner

Spatial and temporal variations in the thermodynamics since the Last Glacial Maximum at Jutulstraumen drainage basin, East Antarctica - Rolstad, Cecilie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2006)
Publisher: Routledge
Keywords: Antarktis; akkumulasjon; glasiologi; isstrøm; nunataker

A geochronological and geochemical study of rocks from Gjelsvikfjella, Dronning Maud Land, Antarctica—implications for Mesoproterozoic correlations and assembly of Gondwana - Paulsson, Oskar; Austrheim, Håkon (Precambrian Research, 2003)
The Jutulsessen nunataks (72°00′S; 2°30′E), Gjelsvikfjella, Dronning Maud Land (DML), consist mainly of migmatites of two types. A heterogeneous banded amphibolite facies gneisses and a more homogeneous part. In the more homogeneous part, partial melts form along axial planes to tight folds. Numerous pegmatitic dykes occur in both migmatites. The homogeneous part of the migmatite has a granodiorite composition. It displays the depletion of Nb–Ta typical for rocks from destructive plate margins and a strongly fractionated REE pattern, specially in LREE (La/Lu ratios varying between 500 and 800). SIMS dating of zircon from the homogeneous migmatite and two pegmatite dykes resulted in two age groups. A concordant age of 1163±6 Ma is calculated from zircon crystals with no rim/core structure and from cores from structurally complex crystals. This age represents the age of the protolith of the migmatite. A Cambrian age of 504±6 Ma is obtained from zircon rims and from sector-zoned zircons. This age represent the time of migmatisation. Sm–Nd depleted mantle model ages range from 1390 to 1770 Ma and suggest that the protolith to the migmatites contained components of older crust (pre-1163 Ma). An igneous complex consisting of a syenite plug (Stabben syenite), gabbroic rocks and aplitic dykes intrudes the metamorphic complex. The syenite and the aplitic dykes are neither deformed nor migmatised or penetrated by pegmatitic dykes. These rocks have elevated LREE and LILE concentrations with an La/Lu ratio of 450 and an Nb–Ta trough. The gabbroic rocks range in composition from melagabbro to monzogabbro and host numerous pegmatitic dykes. SIMS zircon U–Pb data from the Stabben syenite give an age of 500±8 Ma. This age is regarded as the intrusive age of the Stabben syenite. By the single zircon–Pb evaporation method an age of 495±14 Ma is obtained from the aplitic dykes. Sm–Nd depleted mantle model ages between 1800 and 2220 Ma indicate that the dykes formed from a Paleoproterozoic source. A Mesoproterozoic volcanic arc setting of DML and a correlation with the Natal Province, as suggested by several authors, is supported by data in this study. The studied area has consequently been a part of the Kaapvaal/Kalahari craton since Mesoproterozoic time. The Cambrian migmatisation and the intrusions are interpreted as a result of post-collision activity related to the collision between the Kalahari craton and the combined block of Antarctica and Australia during the final assembly of Gondwana. This collision is suggested to be included in the Kuunga Orogeny introduced by Meerat and Van der Voo [J. Geodynam. 23 (1997) 223].
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geokronologi; geologi; nunataker; petrologi

Cryogenic grooves on a granite nunatak, Northern Victoria Land, Antarctica - French, Hugh; Guglielmin, Mauro (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2002)
Publisher: Routledge
Keywords: Antarktis; glasiologi; nunataker

The influence of ornithogenic products on the nutrient status of soils surrounding nests on nunataks in Dronning Maud Land, Antarctica - Cocks, Martin P; Harris, Jean M; Steele, William K; Balfour, Dave A (Polar Research, 1999)
Keywords: Dronning Maud Land; fugler; nunataker; næringsstoff; ornitologi; petreller